Protein Disulfide Isomerase-associated 6 is an ATF6-inducible ER Stress Response Protein that Protects Cardiac Myocytes from Ischemia/Reperfusion-mediated Cell Death - Vekich, John A. (2012)
Proper folding of secreted and transmembrane proteins made in the rough endoplasmic reticulum (ER) requires oxygen for disulfide bond formation. Accordingly, ischemia can impair ER protein folding and initiate the ER stress response, which we previously showed is activated in the ischemic heart and in culture cardiac myocytes subjected to simulated ischemia. ER stress and ischemia activate the transcription factor, activating transcription factor 6 (ATF6), which induces numerous genes, many of which have not been identified, or examined in the heart. Using an ATF6 transgenic mouse model, we previously showed that ATF6 protected the heart from ischemic damage; however, the mechanism of this protection remains to be determined. In this study, we showed that, in the mouse heart, and in cultured cardiac myocytes, ATF6 induced the protein disulfide isomerase associated 6 (PDIA6) gene, which encodes an ER enzyme that catalyzes protein disulfide bond formation. Moreover, in cultured cardiac myocytes, ER stress-mediated PDIA6 promoter activation was ATF6-dependent, and required an ER stress response element (ERSE) and a nearby CCAAT box element. Electromobility shift assays and chromatin immunoprecipitation showed that ATF6 bound to the ERSE in the PDIA6 promoter, in vitro, and in the mouse heart, in vivo. Gain- and loss-of-function studies showed that PDIA6 protected cardiac myocytes against simulated ischemia/reperfusion-induced death in a manner that was dependent on the catalytic activity of PDIA6. Thus, by facilitating disulfide bond formation, and enhanced ER protein folding, PDIA6 may contribute to the protective effects of ATF6 in the ischemic mouse heart.